Green Synthesis of Silver Nanoclusters for Sensitive and Selective Detection of Toxic Metal Ions - Sayed M. Saleh; Shahad Altaiyah; Reham Ali (Analytica)
This research introduces a novel synthetic method for introducing highly luminescent silver nanoclusters (AgNCs). The technique relies on coffee Arabica seed extraction (CSE), which is the focus of this study. Our developed and manufactured ecologically friendly approach has enhanced the selectivity of AgNCs for Hg(II) ions. The coffee extract was employed in the synthesis process to stabilize and enhance the quantity of AgNCs generated. Various advanced techniques were used to characterize the AgNCs precisely in their prepared condition concerning size, surface modification, and composition. The fluorescence quenching of the AgNCs was the mechanism via which the CSE-AgNCs reacted to the principal metal ions in the experiment. Using this sensing methodology, a very accurate and selective sensing method is provided for Hg(II) in the dynamic range of 0.117 µM to 1.4 µM, with a limit of detection (LOD) equal to 35.21 nM. Comparative research was conducted to determine how selective CSE-AgNCs are for Hg(II) ions compared to other ions. Consequently, a notable degree of selectivity of AgNCs towards these Hg(II) metal ions was achieved, allowing the sensitive detection of Hg(II) metal ions, even their interfering metal ions, in the environment. AgNCs can detect Hg(II) at acceptable values within the nanomolar range. Based on their characteristics, Hg(II) ions were detected in real samples using CSE-AgNCs.